Evaluasi Kurikulum Merdeka Terhadap Peluang SNPMB Melalui Jalur SNBP dan SNBT: Studi Kasus di SMA Muhammadiyah 1 Palembang - Sandia Pratama; Reva Aulia (Journal of Contemporary Public Administration, 2026)
This study examines the dynamics of the education system in Indonesia after the COVID-19 pandemic as reflected in the education curriculum. In response to these changes, the government, introduced the Merdeka Curriculum as an effort to structurally reform the 2013 curriculum. This effort has caused major changes in the world of education, especially the adaptation to new learning methods that can reduce student performance. This also has a direct impact on the preparation for the New Student Admission election for high school students. Therefore, this study aims to evaluate the implementation of the Merdeka Curriculum on the opportunities for the National Selection for New Student Admission with a focus on the National Selection Based on Achievement (SNBP) and National Selection Based on Tests (SNBT) pathways. The research method used is a qualitative approach with a case study strategy, which allows for in-depth exploration. Data was collected through in-depth interviews with teachers and students as well as SNBP and SNBT graduation data for 2023–2025. Data analysis was conducted thematically by grouping findings based on main themes. The results showed that the Merdeka Curriculum provides flexibility in learning through a differentiated approach and the Pancasila Student Profile (P5) project. However, its impact on SNPMB opportunities has not been optimal. This is due to teachers' lack of understanding of the essence of P5, the implementation of projects that tend to be administrative in nature, and the freedom to choose subjects that are not yet aligned with SNBP eligibility requirements. On the other hand, the Merdeka Curriculum learning approach has proven to be more supportive of students' readiness for the SNBT pathway, which emphasizes reasoning, literacy, and numeracy skills. Therefore, continuous evaluation and harmonization between curriculum policies and higher education selection systems are needed so that the goals of improving quality and equalizing access to education can be achieved in a balanced manner.